Marsupial extension in terrestrial isopods (Crustacea, Isopoda, Oniscidea) - Carina Appel; Aline F. Quadros; Paula B. Araujo (Nauplius)
In Oniscidea, the marsupium is a ventral pouch where the offspring develop independently of an external water source. The marsupium is formed by five pairs of overlapping oostegites that develop in the females during their reproductive period. In this study, ovigerous females of 35 species were dissected, their oostegites were extracted, and the intra-marsupial offspring were counted. Two marsupium forms were recognized: distended, in which the oostegites protrude distally in relation to the sternites; and non-distended, in which the oostegites are parallel to the sixth and seventh sternites. Armadillidium nasatum, A. vulgare, Pudeoniscus birabeni, Circoniscus gaigei and Cubaris murina, conglobating species with a non-distended marsupium, and Neotroponiscus daguerri and N. carolii, non-conglobating species with a distended marsupium, have a concavity on the ventral floor of the 6th and 7th pereionites, here called the marsupial extension. This is the first record of a marsupial extension which extends beyond the area formed by the oostegites in Oniscidea.